Relapse Kala-azar: A potential threat to sustaining public health elimination in Bangladesh and ways to overcome it (Journal of Medicine, 2025)
Leishmaniasis is a cluster of zoonotic diseases caused by more than 20 species of Leishmania parasites. It manifests in three primary clinical forms: visceral, cutaneous, and mucocutaneous leishmaniasis. Visceral leishmaniasis is the gravest form, which is endemic in Bangladesh. Bangladesh experiences the highest number of cases between 1993 and 2005, affecting 45 districts across the country. Over the years, Bangladesh has successfully reduced its burden through the effective implementation of the National Kala-azar Elimination Program (NKEP) since 2008, resulting in the country becoming the first in the world to achieve the historic milestone of a public health elimination certificate from the WHO.At this stage, prevention of transmission and eradication of parasites are the cornerstones in sustaining the public health elimination status. Relapse kala-azar (RKA) patients (single and multiple) are the potential threat to achieving this, as RKA patients act as an archive or repository for the L. donovani parasite.This review highlighted the potential risk factors of RKA, challenges associated with RKA, and possible solutions for mitigating outbreaks of RKA. Male gender, younger population, immunocompromised status, shorter regimen of treatment, splenomegaly, cytopenia, malnutrition, and poor socioeconomic status are the common risk factors. Significant challenges to be encountered are asymptomatic carriers, parasitological confirmation, availability of drugs, potential drug resistance, and the appearance of cases (refractory KA, Para-Kala azar dermal leishmaniasis) that are difficult to treat. The increasing availability of molecular diagnosis and xenodiagnosis, longer treatment regimens (multidose, combination, and secondary prophylaxis), the availability of drugs, and the development of new molecules may be possible solutions for the effective management of RKA, which is crucial for sustaining public health elimination of KA in Bangladesh. It is now time to update the clinical case management guideline and revise the dose of LAmB to 15 mg/kg in divided doses.The provision of secondary prophylaxis needs to be added in the guideline for treating RfKA and para-KDL cases.J MEDICINE 2025; 26(2): 131-141